Academic and clinical performance among nursing students: What's grit go to do with it?. (May 2020) - Terry, Daniel; Peck, Blake
Abstract: Background: Nursing is both a science and an art and requires students to develop sound scientific foundations for artful application. The at times binary nature of how the way in which the knowledge and skills of nursing are delivered in higher education can be difficult for students to comprehend initially and synchronise for practice and can lead to feelings of being overwhelmed, withdrawal or failure. Understanding what influences student performance in bachelor level nursing studies is imperative so educators can develop programs that straddle the art and science conundrum and lead to graduate success. Grit is a non-cognitive trait, a drive that keeps an individual on task through difficult circumstances for sustained periods of time. Grit might well represent a key factor in our understanding of why one student succeeds while another withdraws. Objectives: To examine measures of grit in the context of demographic characteristics of nursing students and their impact on student self-perceived academic and clinical performance. Design: A cross-sectional design. Setting: A single School of Nursing at a multi-campus, regional, peri-urban Australian University. Participants: All nursing students ( n  = 2349) studying a three-year bachelor of nursing degree were invited to participate. Methods: Data were collected using a questionnaire that included several demographic items, questions relating to the student's perceived level of academic and clinical performance, and the eight-item Short Grit Scale (Grit-S) used to measure trait-level perseverance and passion for long-term goals. Results: Students, regardless of their year of study or any other demographic factor, showed grit was the only significant predictor of clinical and academic performance. Conclusions: The strength between grit and perceived performance both academically and clinically, makes grit a valuable factor for development in students as a vehicle for success in nursing programs of study. This paper culminates in suggestions for creative approaches to grit development.